2021
DOI: 10.1016/j.hrthm.2021.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix remodeling precedes atrial fibrillation: Results of the PREDICT-AF trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…We recently reported that an upregulation of glycoproteins and proteoglycans may even precede the first onset of AF. 6 These findings suggest that changes in ECM composition and morphology may be an early, dominant feature of ECM remodeling in AF.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…We recently reported that an upregulation of glycoproteins and proteoglycans may even precede the first onset of AF. 6 These findings suggest that changes in ECM composition and morphology may be an early, dominant feature of ECM remodeling in AF.…”
Section: Discussionmentioning
confidence: 88%
“…We lately reported that signs of atrial EMT may even precede the first occurrence of incident AF. 6 The re‐activation of quiescent epicardial cells has long been recognized in lower vertebrates such as zebrafish 38 and has been described in the setting of acute myocardial infarction. 39 However, EPC re‐activation was only recently reported in association with fibro‐fatty infiltration in mitral valve disease‐related AF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the degree of collagen crosslinking was associated with cardiac function. A more compliant and less stiff collagen fibers would hinder the force development of the myocytes and disrupted the systolic function of hearts ( 13 ). Taken together, collagen fibers in the cardiac extra cellular matrix (ECM) contribute to keeping the rigidity and the architecture of hearts ( 12 ).…”
Section: Introductionmentioning
confidence: 99%